Interregional demographic aging and migration of the elderly in New Zealand - L.D.B. Heenan; Kevin Moffat (Asia-Pacific Population Journal, 1986)
Elderly people (those 65 years of age or older) comprise one of the largest and most rapidly expanding minorities in New Zealand. Since 1945, their number has more than doubled, from 147,219 to 316,197 (de facto definition) in 1981.